Novel technique of tetra trephination for elliptical-shaped tectonic patch grafts in peripheral sterile keratolysis. Issue 5 (September 2021) - Bafna, Rahul Kumar; Kalra, Nidhi; Asif, Mohamed Ibrahime; Agarwal, Rinky; Lata, Suman; Titiyal, Jeewan Singh; Sharma, Namrata; Vikas, Shiv Jee
Purpose: To describe a novel technique of tectonic patch grafts for elliptical-shaped peripheral sterile keratolysis with iris prolapse. Methods: We performed a full thickness corneo-scleral patch graft in five eyes of five patients with elliptical-shaped peripheral sterile keratolysis with perforation and iris tissue prolapse. In this technique, four disposable trephines with predetermined diameter were employed to fashion both the host and the donor without any free-hand dissection. An intact anatomical integrity of the globe without the need for any repeat tectonic measures was considered as a successful outcome. Results: The mean age was 34.2 ± 10.2 years (18–45). The mean total surgical time and donor preparation time was 94.4 ± 7.12 min and 7.6 ± 1.14 min, respectively. The intraoperative course was uneventful in all cases and all eyes had a well-maintained corneal integrity till 6 months follow up. Conclusion: We describe a simple, reproducible, and time-saving technique of performing elliptical shaped corneoscleral patch grafts for peripheral corneal perforations with iris prolapse.